Effect of sweet solutes and potassium sorbate on the thermal inactivation of Z. bailii in model aqueous systems - Gliemmo, María Fernanda (2006)
The effect of solute type (glucose and polyols) and potassium sorbate (KS) on Zygosaccharomyces bailii thermal inactivation was evaluated in acidified aqueous model systems. Thermal inactivation curves obtained were fitted with Baranyi equation and parameters of this model were estimated and used to establish the effect of water activity (aw), solute added and KS on Z. Bailii survival. Results obtained showed that addition of KS (0.025%, w/w) in general promoted an increase in the rate of heat inactivation. The use of polyols to depress aw to 0.985 in the absence of KS produced no effect on rate of heat inactivation. On the contrary, the use of glucose (10%, w/w) enhanced it. This trend was also observed when aw was depressed to 0.971 by glucose or xylitol or glucose-polyols. Moreover, aw depression in systems containing KS produced different effects on thermal inactivation rate depending on system composition. A synergic effect on the rate of inactivation of Z. bailii was observed by the combined use of KS and sorbitol, xylitol or glucose to depress aW to 0.985– 0.988. This behavior might allow to decrease the severity of the thermal treatment with no detrimental effect on sterility.